Induced pesticide tolerance results from detoxification pathway priming. (May 2017) - Oziolor, Elias M.; Howard, Willow; Lavado, Ramon; Matson, Cole W.
Abstract: Few studies in developmental toxicology have focused on whether early life contaminant exposure affects future susceptibility. Investigations in frogs suggested that early life exposure to a pesticide resulted in higher tolerance to a subsequent challenge. This led to the hypothesis that early-life stage exposures can alter phenotypically plastic traits during development, resulting in induced tolerance. Here, we used Gulf killifish ( Fundulus grandis ) to test the role of detoxification pathway priming in this inducible tolerance. In frogs, the induced tolerance is present five days after the end of the pre-exposure, but absent after a month. We show that a pre-exposure early in life with carbaryl, induces the activity of cytochrome P450 1A (CYP1A) and increases the ability of pre-exposed groups to metabolize carbaryl, likely because of activation of the aryl hydrocarbon receptor (AHR) pathway. Embryos pre-exposed to carbaryl had a 350–500% increase in CYP1A activity, threefold greater capacity to metabolize carbaryl and were more tolerant to a lethal challenge five days after the end of pre-exposure. However, ten days later the differences in CYP1A activity, metabolic capacity and tolerance between pre-exposed and control groups were no longer present. Thus, we conclude that the increase in tolerance observed in pre-exposed fish embryos was due to the activation of the AHR and other metabolic pathways, resulting in a prolonged increase in biotransformation capacity. This allowed individuals to more efficiently deal with subsequent chemical challenges for a short period after the initial pre-exposure. However, this induced tolerance was only short-lived due to the recycling of biotransformation enzymes in the cells as part of general cellular protein maintenance. These findings suggest that induced tolerance was likely due to induction of defense mechanisms during the duration of response to the original stressor, rather than a more permanent change in their ability to respond to future challenges. Graphical abstract: Highlights: Sub-lethal pre-dose of carbaryl causes temporary protection from further challenges. Previously believed to be caused by induced tolerance due to phenotypic plasticity. We show sub-lethal dose causes induction of activity of the protective enzyme CYP1A. While enzyme activity is induced, fish are more tolerant to further doses. When enzyme activity declines to basal levels, tolerance is reduced to basal.